POSTGRADUATE RESEARCH IN PHARMACEUTICAL SCIENCES IN INDIA: A SURVEY OF SELECT PHARMACY PROFESSIONALS - Palsokar, Gouri; Tajne, Madhukar (International Journal of Current Pharmaceutical Research, 2017)
Objective: Research is a systematic investigation that involves the study of materials and sources in order to establish facts and reach new conclusions. Post-graduate pharmaceutical education develops the necessary skills among students which help them build their professional carriers and contribute towards the betterment of the healthcare industry and society in general. Hence, it is essential and mandatory to carry out some appropriate research work as a requirement of post-graduate courses in Pharmaceutical Sciences in India and abroad. In an era, where technology is changing rapidly, the research carried out by students must always be relevant to the present day, so that it can act as a bridge between innovation and utility with regard to patient care and compliance. The present work aims to investigate, as to how, the research at postgraduate level in pharmacy, could be carried out in a way so that it benefits the students and make their research relevant to the current industry needs. Methods: The opinions of academicians from select academic institutions, professionals from pharmaceutical industries and postgraduates and Ph. D. students across India, were collected through questionnaires and by taking personal interviews. Data thus obtained was subjected to standard mathematical interpretations. Results: About 48% (65) of faculty members and 46% (156) of Postgraduate and Ph. D. students from various parts of the country opined that projects in postgraduate courses should be executed partly in academic institutions and partly in industries. However, about 61% (180) respondents from the pharmaceutical industry were of the view that the postgraduate students should undertake industrial projects. At the same time, some professionals were of the view that, students carrying out research work fully in the industry are many times left on their own as their industrial supervisors are unable to spare time to guide them. Conclusion: The execution of research work carried out by post-graduate students should be evenly distributed in academic institutions as well as pharmaceutical industries, under the supervision of faculty and with active inputs from the industry. Â